2004
DOI: 10.1136/thx.2003.013029
|View full text |Cite
|
Sign up to set email alerts
|

No association between interferon-  receptor-1 gene polymorphism and pulmonary tuberculosis in a Gambian population sample

Abstract: Background: Tuberculosis (TB) is a major global cause of mortality and morbidity, and host genetic factors influence disease susceptibility. Interferon-c mediates immunity to mycobacteria and rare mutations in the interferon-c receptor-1 gene (IFNGR1) result in increased susceptibility to mycobacterial infection, including TB, in affected families. The role of genetic variation in IFNGR1 in susceptibility to common mycobacterial diseases such as pulmonary TB in outbred populations has not previously been inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…Association between a SNP in IFNGR1 and disease caused by specifically M. tuberculosis was recently reported in a Gambian population (Cooke et al 2006), though previous analyses of microsatellites within IFNGR1 were inconsistent (Awomoyi et al 2004;Fraser et al 2003). Our analysis independently confirms that of Cooke and colleagues who found the CC genotype at the -56 SNP (rs2234711) to be associated with increased risk for TB disease.…”
Section: Discussionsupporting
confidence: 91%
“…Association between a SNP in IFNGR1 and disease caused by specifically M. tuberculosis was recently reported in a Gambian population (Cooke et al 2006), though previous analyses of microsatellites within IFNGR1 were inconsistent (Awomoyi et al 2004;Fraser et al 2003). Our analysis independently confirms that of Cooke and colleagues who found the CC genotype at the -56 SNP (rs2234711) to be associated with increased risk for TB disease.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary to our results, Varahram et al, did not fi nd any signifi cant association between IFN-γR1-611 SNP and susceptibility to TB among Iranian studied cases [14]. Also, few studies declines the correlation of IFN-γR1 polymorphism with M. tuberculosis infection [18,19]. At present, we have no explanation for such discrepancy, but these observations may outline the alternative pathways for enhancing host immune response against mycobacterial infections.…”
Section: Discussioncontrasting
confidence: 56%
“…In a research conducted recently by Awomoyi et al, regarding interferon gamma receptor-1 gene polymorphism; 16 despite a sample size of 340 TB patients with an equal number in the control group, still significant difference could not be detected between the two groups. This finding was similar to ours.…”
Section: Discussionmentioning
confidence: 67%
“…However, no significant relation was detected. Basically, our study was based on that fact that both the researches that were performed by Awomoyi 16 Although previous studies had shown that locus 395 was a genetic predisposition factor, but it had not been evaluated individually. In other words, different parts of the gene in the intron, extron and promoter regions had been studied in this research as well as in the last two researches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation